THE EMBODIMENT OF LITERARY AND DIALECT FEATURES OF FEMINITATION IN THE NOVELS OF VASYL STEFANYK - Brus, Мariia (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
The article analyzes the common names and surnames of women, which are reflected in the short stories of Vasyl Stefanyk. Attention is paid to the specifics of the writer's artistic work as a representative of the dialect of Pokuttia, the semantic, word-forming, stylistic features of the nouns embodied in his works with the meaning of femininity are revealed. It is noted that the feminicon of his short stories is a close combination of all-literary, Western Ukrainian and Pokuttia lexical units, which is marked by the specifics of the author's artistic vision and immersion in the world of rural life. It is noted that the feminicon of his short stories is a close combination of all-literary, Western Ukrainian and Pokuttia lexical units, which is marked by the specifics of the author's artistic vision and immersion in the world of rural life. The processes of feminization and femininity in Vasyl Stefanyk's work are based on the vernacular, which made it possible to attract all the feminine richness of the then Ukrainian literary language for women's education and its realization along with masculinities. From the lexical-semantic point of view, it is the embodiment of commonly used and special nominations, the expansion of the semantic structure of femininities, and their use with specific meanings. In structural and word-forming terms, it is the realization of derived and non-derived words, the predominance of suffixal word-forming types over other derivatives, the expansion of the functionality of word-forming means. At the stylistic level, it is the accumulation of stylistically neutral and colored vocabulary, giving almost all nouns with the meaning of femininity a colloquial character and different connotative shades in the meaning. Consideration and interpretation of female images was based on deep legislation and the involvement of writers in the realities of Pokuttia life, which led to the integrated use of appropriate names of women.